X-men: red (2022), volume 3 ebook - Ewing, Al (X-Men: Red (2022), 2024)
Collects X-Men Red (2022) #11-13, X-Men: Before the Fall - Heralds of Apocalypse (2023) #1. The calm before the…? After recent turmoil, Arakko catches its breath - but even as Storm begins a new romance, she has no time to rest. Xavier has questions about Magneto's death, and he's not asking nicely. Meanwhile, the White Sword - the Omega mutant healer who could raise the dead and bind them to his service - once had one hundred warriors. Now the last of the Hundred tells the tale of the one who destroyed them - one who is coming to test Arakko again! Plus: The origin of Arakko revealed! In ancient days, Genesis turned back the hordes of Amenth and forced Annihilation into a parley. What words were spoken in her mind? Apocalypse finally will know, and the echoes of those words might destroy him - and Arakko with him!